LANGERHANS HISTIOCYTOSIS-RELATED HYPOPHYSITIS: A DISTINCT CAUSE OF CRANIAL DIABETES INSIPIDUS - Ramiah, Shanthini; Chua, Yi Jiang; Samsudin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Cranial diabetes insipidus (DI) is a rare manifestation of hypothalamo-pituitary axis disorders. Langerhans Cell Histiocytosis (LCH), a clonal disease of dendritic cells, can infiltrate multiple organs, including the pituitary gland. When the posterior pituitary is involved, LCH can cause secondary hypophysitis, leading to cranial DI. Due to overlapping symptoms with more common conditions, diagnosis can be delayed. CASE A 22-year-old female with a one-year history of bullous skin lesions and oral ulcers was initially diagnosed with pemphigus vulgaris and treated with prednisolone. However, a skin biopsy later confirmed LCH. Imaging, including CT of the brain, neck and thorax-abdomen-pelvis, showed multisystem involvement (skin, ear, thyroid, and thymus). Hence, she underwent chemotherapy. After the first cycle of chemotherapy with vinblastine and high-dose dexamethasone, she developed vomiting and lethargy. Laboratory tests revealed a hyperosmolar hyperglycemic state (serum osmolality 323 mOsm/kg). Despite normalisation of her blood glucose, she developed marked polyuria (>13,000 mL/day). Further testing showed serum osmolality of 294 mOsm/kg and urine osmolality of 54 mOsm/kg. A desmopressin trial resulted in a >50% increase in urine osmolality (398 mOsm/kg at 2 hours; 511 mOsm/kg at 4 hours), confirming cranial DI. MRI revealed a 1.1 × 1.3 × 1.0 cm lesion in the pituitary infundibulum, consistent with LCH-related hypophysitis, along with empty sella syndrome, likely secondary to chronic pituitary involvement and glucocorticoid therapy. She was treated with sublingual desmopressin and high-dose steroids, showing clinical improvement. CONCLUSION This case highlights the need to consider cranial DI as a manifestation of systemic LCH, especially in young adults with multisystem disease. Given the overlap of symptoms, early recognition of cranial DI is crucial for timely management.